Weirding the war : stories from the Civil War's ragged edges - Berry, Stephen William (Uncivil wars., 2011)
"It is well that war is so terrible," Robert E. Lee reportedly said, "or we would grow too fond of it." The essays collected here make the case that we have grown too fond of it, and therefore we must make the war terƯrible again. Taking a "freakonomics" approach to Civil War studies, each contributor uses a seemingly unusual story, incident, or phenomenon to cast new light on the nature of the war itself. Collectively the essays remind us that war is always about damage, even at its most heroic and even when certain people and things deserve to be damaged. Here then is not only the grandness of the Civil War but its more than occasional littleness. Here are those who profited by the war and those who lost by it-and not just those who lost all save their honor, but those who lost their honor too. Here are the cowards, the coxcombs, the belles, the deserters, and the scavengers who hung back and so survived, even thrived. Here are dark topics like torture, hunger, and amputation. Here, in short, is war